Mineral Indicators - Alumina (The National Institute for Occupational Safety and Health (NIOSH), 1978)
Kaiser Aluminum & Chemical Corp. announced that it planned to spend $66 million to increase the efficiency of its Baton Rouge, Louisiana, alumina plant. The improvements are designed to reduce energy consumption but will not change the annual capacity of the plant, now rated at about one million short tons. The project was expected to be initiated immediately and be completed by 1982. ALUMINUM Producers in this country posted unalloyed 99.5 percent aluminum ingot at 53-57.5 cents per pound, yet actual selling prices were closer to 53 cents. Domestic merchants quoted unalloyed ingot on a spot basis at 54-56.3 cents. London Metal Exchange 3-month forward contracts fell during November's trading from 55,2 cents to 52.8 cents per pound.